Implementing a Kindness-Based Leadership Strategy in Islamic Elementary Education - Suherman, Usep; Cipta, Eliva Sukma; Anwar, Saeful; Kadir, Wildan Abdul; Fakhrurrozi, M. Fahmi; Namira, Sarah Honsa; Halimatussadiyah, Wafa (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
In the face of increasingly complex educational challenges, there is a growing demand for leadership models that integrate ethical and humanistic values, particularly in Islamic elementary schools. This study explores the operationalisation of kindness-based leadership at MI Fitrah Insani, Leles, Garut, as a strategic response to the limitations of performance-oriented and hierarchical leadership paradigms. This study addresses the gaps in the literature regarding the implementation of ethical leadership grounded in Islamic values by examining how empathy, participatory communication, and ethical responsibility shape school culture and educational quality. Using a qualitative case study approach, data were collected through in-depth interviews, field observations, and a document analysis. Triangulation of these methods enabled a comprehensive understanding of institutional dynamics, leadership practices, and their impact on school climate, teacher motivation, and student engagement. The findings reveal that kindness-based leadership at MI Fitrah Insani fosters an emotionally safe and inclusive school environment. Through participatory decision-making, structured communication, and consistent appreciation practices, the leadership model contributes to improved teacher loyalty, pedagogical innovation, and heightened student participation. Despite structural, cultural, and operational barriers such as bureaucratic rigidity and limited professional development, adaptive strategies, including ethical leadership training, policy reform, and digital communication platforms, have enhanced the effectiveness and sustainability of this model. This study concludes that kindness-oriented leadership is not merely a normative ideal but a transformative practice that aligns with Islamic ethical traditions and addresses the academic and moral dimensions of education. The findings offer practical implications for Islamic schools seeking to cultivate character-driven and ethically grounded leadership.